OBTAINING CELLULOSE BASED ON PAVLONA WOOD AND BANANA STOBLES AND ANALYSIS OF COMPARATIVE CHARACTERISTICS AT DIFFERENT STAGES - Sandybaeva Zamira Hudayberdievna; Murodov Muzaffar Murodovich (Journals Park Publishing, 2022)
Because the soft and delicate structure of the Pavlonia tree does not require a 2-3 step sequence in the synthesis process. During the study, cellulose synthesis was carried out in parallel from samples of Pavlonia wood belonging to different years, i.e. delegnefication process was carried out in an autoclave under high pressure, as well as by hydrolysis at 95-1000C. His research also includes years of research into the synthesis of certain brands of cellulose that are chemically recyclable based on Pavlonia tree stems. It is known that various chemical processes are used during cellulose synthesis. The sodium method was used in this study.In the process of cellulose synthesis, the balance of the 2nd, 4th, and 18-year-old stems of the Pavlonia tree was used to form a ridge.
Keywords: moisture, cellulose, concentration, pentosan, alkali sediment, suffocation, ash content